Determination of Chemical Properties of Walnut (Juglans regia L.) Cultivars Grown in Turkey - Akca, Yasar; Sutyemez, Mehmet; Ozgen, Mustafa; Tuzen, Mustafa; Mendil, Durali (Asian Journal of Chemistry, 2016)
Potassium, phosphorus, magnesium and iron are found in significant quantities in Persian walnuts (Juglans regia). The concentrations of some of the nutrients of different walnut cultivars were determined by flame atomic absorption spectrometry after microwave digestion. Major nutrients found in these cultivars were in the range of 170-419 and 102-146 mg/100 g for potassium and magnesium respectively. The contents of other minerals found were between 202-453 for calcium, 1.2-6.9 for iron, 1.2-3.8 for zinc, 0.5-2.2 for copper, 0.4-3.5 for sodium and 1.2-6.0 for manganese as mg/100 g.